Genomic extraction of several Malaysian herbal plants - Rahmat, Zaidah; Ramli, Aizi Nor Mazila; Abd. Aziz, Izza; Liew, Woon Mee; Almalek Fuat, Noor Afida; Muhammad Zaidi, NorFadzilah; Kamaruzaman, Nor Kamila; Pua, Swee Siang; Mohd., Azrul Razi; Mohd. Dani, Siti Marziah; Zakaria, Zahirah (2006)
Herbal plants are found in abundant in Malaysian rain forests with various uses for its medicinal, pharmaceutical and nutritional value as well as the ordinary spice in our culinary. Among herbal plant studied include Java Tea, "Senduduk (purple & white)", "Daun Kaduk", Madagascar Periwinkle, Gardenia, Impatiens and Betel. As genomic DNA extraction method for each plant varies according to its properties and constituents, four extraction methods were chosen to determine the best method for each species. The methods selected were Doyle and Doyle Method (1989), Dellaporta et al. Method, Modified CTAB Method, and DNA and RNA Double Extraction Method. Modified CTAB Method was determined as the best extraction method for most of the plant studied except for one. Genomic DNA for Betel was best extracted using the Doyle and Doyle Method. The results obtained from the study varied for each plant and it proved that the constituents in each plant species contributed to the success of extracting genomic DNA of high quality and purity even from two closely related species such as "Daun Kaduk" (Pipersarmentoum Roxb.) and Betel (Piper betel Linn).